Assessment Instrument of Social Attitude and Science Learning Outcomes of Grade IV Elementary School - Agus Pujawan, I Ketut Adi; Astawan, I Gede (Universitas Pendidikan Ganesha, 2020)
The implementation of this research is based on the unoptimized assessment instrument, which is the instrument of social attitudes and students science learning results in accordance with the assessment standards. This study aims to produce instruments for assessing social attitudes and learning outcomes of valid and reliable Natural Sciences in Theme 8 of Grade IV elementary school. This research is a development study carried out using the 4D model with 4 stages including: define, Â design, development, dissemination, but the dissemination phase is not carried out due to time constraints. Data collection methods used were questionnaires and multiple choice tests. The instrument developed to measure social attitudes was a questionnaire while the instrument developed to measure science learning outcomes was a multiple choice test. This instrument was validated by two experts in the field of social attitudes and science. The results showed the content validity of the social attitude questionnaire and the science learning outcomes were very high with a value of 1.00. The item validity test showed that of the 30 items on the social attitude questionnaire, 28 questions were declared valid, while out of the 30 items on the test of science learning outcomes 25 items were valid. The results of the reliability of the social attitude instrument were stated to be very high with a value of r1.1 = 0.88 and the reliability of the science learning outcomes test was also very high with a value of r1.1 = 0.82. The different power of the Natural Science learning outcomes test instrument is expressed in good criteria with a value of 0.74, while for the difficulty level is in the medium criteria with a value of 0.65. These results indicate that the instrument for evaluating social attitudes and science learning outcomes is expressed in good qualifications and is suitable for use.